2016
DOI: 10.1002/2015jd024181
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor‐weighted mean temperature and its impact on the determination of precipitable water vapor and its linear trend

Abstract: Water vapor‐weighted mean temperature, Tm, is a vital parameter for retrieving precipitable water vapor (PWV) from the zenith wet delay (ZWD) of Global Navigation Satellite Systems (GNSS) signal propagation. In this study, the Tm at 368 GNSS stations for 2000–2012 were calculated using three methods: (1) temperature and humidity profiles from ERA‐Interim, (2) the Bevis Tm–Ts relationship, and (3) the Global Pressure and Temperature 2 wet model. Tm derived from the first method was used as a reference to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 80 publications
(146 reference statements)
2
120
0
Order By: Relevance
“…This research is part of our continuous effort to extend our research presented in Wang et al (2016a) by investigating the alternative methods for the determination of ZHD and developing of a new global long-term IWV time series, which is critical for an improved understanding of climate change using the state of the art GNSS technology. In this study, the accuracies of the ERA-Interim-derived surface pressure (calculated from the nearest grid point and interpolated from four surrounding grid points) and GPT2w-derived 6 h pressure have been investigated by comparing them against the observed pressure for 108 stations during the period 2000-2013.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This research is part of our continuous effort to extend our research presented in Wang et al (2016a) by investigating the alternative methods for the determination of ZHD and developing of a new global long-term IWV time series, which is critical for an improved understanding of climate change using the state of the art GNSS technology. In this study, the accuracies of the ERA-Interim-derived surface pressure (calculated from the nearest grid point and interpolated from four surrounding grid points) and GPT2w-derived 6 h pressure have been investigated by comparing them against the observed pressure for 108 stations during the period 2000-2013.…”
Section: Discussionmentioning
confidence: 99%
“…More details about the computation of have been published in Wang et al (2016a), and here only a brief description of the calculation of is given. As a function of T m , can be calculated using…”
Section: Computation Of Zhd and Iwvmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus the accuracy of this parameter introduces an error in the trend estimates (Nilsson and Elgered, 2008). Recent extensive studies by (Wang, 2016) have demonstrated that depending on the choice of the source of the water vapour mean temperature parameter, the IWV trend shows a relative error larger than 10 %. Thus, for consistency ZTD should be converted to IWV once it has been assimilated and we argue that this would also be the best way forward for climate models.…”
mentioning
confidence: 99%